2015
DOI: 10.1007/s10544-015-9973-6
|View full text |Cite
|
Sign up to set email alerts
|

Fluidic system for long-term in vitro culturing and monitoring of organotypic brain slices

Abstract: Brain slice preparations cultured in vitro have long been used as a simplified model for studying brain development, electrophysiology, neurodegeneration and neuroprotection. In this paper an open fluidic system developed for improved long term culturing of organotypic brain slices is presented. The positive effect of continuous flow of growth medium, and thus stability of the glucose concentration and waste removal, is simulated and compared to the effect of stagnant medium that is most often used in tissue c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Our results indicated that the constant circulation of culture medium at a low speed was associated with a longer lifespan of cells of the brain stem in organotypic culture. Our findings are comparable to successful results of the microfluidic and microperfusion systems used in the cultivation of organotypic cortical and hippocampal slices 26,27 , as we see adequate cell survival for several days 28 , but our methodology offers the advantage of incorporation of a completely autonomous and easy to use system.…”
Section: Discussionsupporting
confidence: 85%
“…Our results indicated that the constant circulation of culture medium at a low speed was associated with a longer lifespan of cells of the brain stem in organotypic culture. Our findings are comparable to successful results of the microfluidic and microperfusion systems used in the cultivation of organotypic cortical and hippocampal slices 26,27 , as we see adequate cell survival for several days 28 , but our methodology offers the advantage of incorporation of a completely autonomous and easy to use system.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, endothelial barriers and interstitial pressure can also be mimicked in the more elaborate versions of these cancer-on-chip set-ups [ 80 ]. Thereby, the maximum time that slices remain vital in culture could be expanded and cultivation will be more high-throughput compared with original organotypic tissue slice cultures [ 81 ]. Optimization of the exact geometry and growth conditions of these microfluidics set-ups hold great promise for tumor slice culturing and development of predictive diagnostic assays.…”
Section: Cancer-on-chipmentioning
confidence: 99%
“…Applying the open fluidic concept, a fluidic system was created to improve long-term in vitro culturing and monitoring of organotypic brain slices [120]. The platform was built using polycarbonate by micromilling and was constituted of two levels.…”
Section: Perfusion System For Cell Culturementioning
confidence: 99%
“…The upper level consisted in a hole to accommodate a porous membrane insert in the culturing area, where the slices of tissue were placed. Due to the continuous perfusion of cell culture medium, the brain slices were cultured for longer periods with reduced handling of the tissues during culturing, and the in vivo-like environment could be better mimicked [120].…”
Section: Perfusion System For Cell Culturementioning
confidence: 99%